Integrative study of Gerbillinae rodents from anthropogenic zones of Northern Morocco: morphometric and molecular approach - (:unkn) unknown (My University, 2020)
Gerbilline rodents represent an important component of the North African and Moroccan mammalian fauna. However, many gaps remain in the understanding of the systematics, distribution, biology, ecology and evolution of certain species. We have targeted in this work a few species of the genera Gerbillus and Meriones captured in northern Morocco and in anthropized areas. We have approached the taxonomy, systematics, phylogeny, biogeography and distribution of these species, with an integrative approach combining the studies of morphology and genetics. The morphological study was based on classic morphometrics using 18 body and cranio-mandibular measurements to carry out descriptive and multivariate statistical analyzes. The genetic study was based on the cytochrome b gene of mitochondrial DNA, which was used in analyzes of genetic diversity and distance, maximum likelihood and haplotype networks. For Gerbillus campestris, a potential agricultural pest, the geographic structuring of six Moroccan populations has produced significant morphological differentiation and high levels of genetic divergence which allow their discrimination into four groups. Concerning the three other species of the genus Gerbillus studied in this work (Gerbillus simoni, Gerbillus henleyi, Gerbillus amoenus), we performed their first genetic characterization in Morocco and we provided additional elements concerning their taxonomy and systematics in North Africa. For the jirds species complex Meriones shawii/grandis, reservoirs of cutaneous leishmaniasis and major agricultural pests, the geographic structure, the morphological differentiation and the genetic divergence that we have obtained support the existence of two distinct species. The precise characterization and reconstruction of the biogeographical history of these species will allow to better understand of the evolution of Gerbillines, conserve the most vulnerable species and put in place more effective control strategies ag
Keywords: African Research